2019
DOI: 10.5185/amlett.2019.9907
|View full text |Cite
|
Sign up to set email alerts
|

Natural Fibers as Viable Sources for the Development of Structural, Semi-Structural, and Technological Materials – A Review

Abstract: A systematic and critical review on the potentials and viability of naturally occurring fibers as suitable reinforcements for the development of composite systems for structural, semi-structural and technological materials is presented in this article. Globally, the movement towards greater protection of the environment and the use of cost-saving technologies has led to a surge in the consideration of natural (biodegradable) products for the development of technological materials. In this regard, natural fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 69 publications
0
6
0
1
Order By: Relevance
“…However, the incorporation of alfa fibers in the epoxy resin allows to use as a conductor, from the dielectric results obtained, the composites based on alfa fiber of the epoxy matrix has a certain dielectric permittivity at low frequency, which makes them applicable in electrical and electronic devices, 37 Nayak et al, 38 reported that natural fiber reinforced composites are fit for electrical and electronic purposes because of their high dielectric properties.…”
Section: Resultsmentioning
confidence: 99%
“…However, the incorporation of alfa fibers in the epoxy resin allows to use as a conductor, from the dielectric results obtained, the composites based on alfa fiber of the epoxy matrix has a certain dielectric permittivity at low frequency, which makes them applicable in electrical and electronic devices, 37 Nayak et al, 38 reported that natural fiber reinforced composites are fit for electrical and electronic purposes because of their high dielectric properties.…”
Section: Resultsmentioning
confidence: 99%
“…Sin embargo, la crisis ambiental que se vive en este momento, provocada por el crecimiento industrial indiscriminado, ha aumentado el interés en la investigación y uso a nivel industrial de fibras provenientes de recursos naturales y renovables [6,7]. De esta forma, fibras de origen animal o vegetal [8] se emplean como refuerzo de materiales compuestos, principalmente con matriz polimérica. La revisión presentada en este artículo se centra en las fibras de origen vegetal, las cuales se llamarán "fibras naturales" de forma general.…”
Section: Introductionunclassified
“…Although pure PP can be used as thermal insulation and sound insulation materials, the mechanical properties are not sufficiently high for many applications. [20][21][22] In this regard, PP is usually filled with rigid inorganic particles, such as talc, [20] glass microspheres [23] or calcium carbonate, [24] fibers, [25][26][27] wood powder, [28,29] and rubber particles [30] to further enhance the mechanical properties. After the addition of hemp wood fibers to polypropylene, the modulus and water absorption of the composites were enhanced, without mentioning the analysis of the density.…”
Section: Introductionmentioning
confidence: 99%